Natural Immunostimulants for Broilers: Evaluating Herbs and Alternative Materials (Indian Journal of Animal Production and Management, 2026)
People are paying more attention to using natural immunostimulants with broilers because they want organic poultry and worry about antibiotic resistance. This research examines how well selected herbs (turmeric, garlic, and oregano) and alternative ingredients (probiotics and yeast extracts) function as natural immunostimulants in chicken food. There were 300 broilers used, with each group receiving one of six diets or the control diet. The researchers examined indicators of growth performance, immune function, and health of the gut. Researchers found that disease-affected animals given turmeric and probiotics responded with much better weight gain, an improved feed conversion ratio (FCR), and higher antibody titers. The results imply that natural immunostimulants can make broilers healthier and more productive, all while preserving safety and sustainability.
Keywords: Natural Immunostimulants; Broilers; Alternative Materials